Feasibility of conducting a randomized clinical trial using family‐based treatment for avoidant/restrictive food intake disorder. Issue 6 (29th March 2019) - Lock, James; Sadeh‐Sharvit, Shiri; L'Insalata, Alexa
Abstract: Treatments for avoidant/restrictive food intake disorder (ARFID) lack strong empirical support. There is a critical need to conduct adequately powered studies to identify effective treatments for ARFID. As a first step, the primary aim of this study was to assess the feasibility of conducting a randomized clinical trial (RCT) comparing Family‐based Treatment for ARFID (FBT‐ARFID) to usual care (UC). The primary outcomes were recruitment, attrition, suitability, and expectancy rates. The secondary aim was to assess changes in percent estimated body weight, eating related psychopathology, and parental self‐efficacy from baseline to end of treatment/UC period in both groups. Recruitment rates were 1.87 per month; 28 children with ARFID and their families were randomized and attrition rate was 21%. Therapeutic suitability and expectancy rating suggested that FBT‐ARFID was acceptable to families. Effect size (ES) differences on measures of weight and clinical severity were moderate to large, favoring FBT‐ARFID over UC. Parental self‐efficacy improvement also demonstrated a large ES favoring FBT‐ARFID, which was correlated with improvements in ARFID symptoms. There is a research gap between our knowledge base on how to treat children with ARFID and clinical need. The data presented suggest that an RCT comparing FBT‐ARFID and UC is feasible to conduct.